Question Items of Magnitude and Motion Topics in Several High School Physics Textbooks: A Cognitive Level Analysis - Lubis, Deli Anggraeni; Nurlina, Nurlina; Marisda, Dewi Hikmah; Riskawati, Riskawati (FKIP Universitas Lampung, 2022)
This study aims to analyze the percentage of cognitive achievement level questions and compare cognitive level achievement based on thinking stages (LOTs and HOTs) in physics textbooks for class X SMA for the content of magnitude and motion. This type of research is descriptive research with a case study design that is analyzed qualitatively. The source of the data in this study was a class X physics textbook on magnitude and motion. The research subjects were evaluation questions in five books, hereinafter referred to as book A, book B, book C, book D, and book E. The results of this study indicated that the highest proportion of cognitive levels used in the questions from the five physics books was C4 (analyzing). and the lowest is C6 (create). The percentage of questions for each cognitive level are: C1 (remembering) 10%, C2 (understanding) 26.85%, C3 (applying) 18%, C4 (analyzing) 51.2%, C5 (evaluating) 5.75% and C6 (create) with a percentage of 0%. This shows that the percentage of HOTS cognitive level items (56.95%) is higher than the LOTs level (43.05%). It is hoped that the results of this study will provide information to high school teachers and prospective physics teacher students to develop practice questions that are oriented towards high-level skills. Keywords: textbook analysis, HOTs, LOTs, cognitive level. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1481-1492